Ratcheting Fatigue of Superalloy IN-617 Under Tensile Mean Stress at RT - Mishra P.; Srinivas N.C.S.; Sastry G.V.S.; Singh V. (My University, 2025)
IN-617 is a superalloy of nickel, primarily used as tubes of superheater, re-heater and steam generator in nuclear core because of its excellent performance in that environment. However, during service the length of tubular components progressively increases due to tensile mean stress resulting from the asymmetric cyclic stressing and the components fail in much smaller number of cycles than that tested under symmetric loading (without tensile mean stress). The present investigation deals with cumulative plastic strain arising under different levels of mean stress (σm), amplitude of stress(σa), and rate of stress (σ˙); and their effect on fatigue life. While the accumulation of permanent deformation enhances with rise in σm and σa and the number of cycles to failure (Nf) decreases, there is opposite effect of σ˙ the permanent strain is decreased from rise in σ˙ and cyclic life is enhanced. TEM analysis of tested samples showed variation in dislocation substructures developed under the different variables. © 2022, The Indian Institute of Metals - IIM.